SISTEM PENGOLAHAN NILAI RAPOR SISWA DI SMKN 3 SUKOHARJO - Joko Prasetyo; Dwi Retnoningsih (JURNAL GAUNG INFORMATIKA, 2014)
The rapid development of current technology make school participate institution developedfollowing period. Especially in the Vocational High School (SMKN) 3 Sukoharjo. SMKN 3 Sukoharjostill using manual method in data processing of data in particular student report cards. In this researchresearcher completed the application program processing of student report cards with the aim ofprovide a solution to undertake processing of them.The application processing of student report cards is divided into two actors are admin and user.Admin can access all the data while the user can perform maintenance access and print the value of thesubject value. The application processing of student report cards were tested using method of McCall to getquality value 77.2%. According to the test results expected report cards processing of applications usedand performance of employees and assist teachers in SMKN 3 Sukoharjo to minimize errors in data processing.